Ship energy performance study of three wind-assisted ship propulsion technologies including a parametric study of the Flettner rotor technology. (15th March 2020) - Lu, Ruihua; Ringsberg, Jonas W.
ABSTRACT: A 4 degrees of freedom ship performance prediction model is used to compare wind-assisted ship propulsion technologies: the Flettner rotor, a wingsail and the DynaRig concept. An Aframax Oil Tanker on a route between Gabon and Canada is used in a case study to compare the three technologies using actual information for the voyage. The fuel savings for were calculated and they varied between 5.6% and 8.9%; the Flettner rotor showed the largest fuel savings. A parametric study of the Flettner rotor technology was carried out to research how its dimensions and operation conditions for two ship types on two voyages influence the fuel savings. The results show that fuel savings were achieved by several percentages. It is shown that it is necessary to select and operate the Flettner rotor according to its ship type, speed, voyage routes and corresponding weather conditions to achieve as large fuel savings as possible.